The Correlation Between Being Informed on Complementary and Alternative Medicine and Its Reported Use Among Cancer Patients in Yogyakarta - Ike Wuri Winahyu Sari; Dwi Kartika Rukmi (Universitas Muhammadiyah Yogyakarta, 2021)
Background: Previous studies have indicated that the majority of cancer patients have used self-selected Complementary and Alternative Medicine to relieve disease-related symptoms and treatment-related adverse effects untreated by conventional treatment to improve the quality of life. Unfortunately, studies on Complementary and Alternative Medicine use among cancer patients, especially in Yogyakarta, the city with the highest cancer prevalence in Indonesia, are still limited.Objective: This present study aims to identify the correlation between being informed on Complementary and Alternative Medicine and its reported use among cancer patients.Methods: This study was a descriptive correlational study on 75 consenting cancer patients. The respondents were selected using a purposive sampling technique. Data about their Complementary and Alternative Medicine use were collected by administered questionnaires and analyzed using descriptive statistics and bivariate analysis.Results: 25.3% of respondents had used Complementary and Alternative Medicine. Being informed on Complementary and Alternative Medicine and its reported use among cancer patients were significantly correlated (r=0.331; p=0.002).Conclusion: Complementary and Alternative Medicine use among cancer patients was still limited. Health providers need to discuss Complementary and Alternative Medicine use with their patients openly.